2013
DOI: 10.1016/j.jbusres.2012.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and R&D workers' multiple commitments: Do justice and span of control matter?

Abstract: This study examines how transformational leaders influence research and development (R&D) workers' commitment to their organizations and leaders. The study investigates the mediating role of organizational justice (i.e., procedural and interactional) based on social exchange theory and the moderating role of span of control in this relationship. In a sample of 445 Turkish R&D personnel, the study finds that transformational leadership significantly influences followers' organizational commitment partially thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 76 publications
(110 reference statements)
2
38
0
2
Order By: Relevance
“…For example, job stress is also found to be predicted by psychological contract [1] (Bocchino, Hartman, & Foley, 2003). Further, the relationship between psychological contract and organizational commitment is also found in previous studies [2] (Gumusluoglu, Karakitapoglu-Aygun, & Hirst, 2013) [3] (Eslami & Gharakhani, 2012). For example, study conducted by [4] ( Lemire & Rouillard, 2005) investigated the relationship between psychological contract violation and organizational commitment in the context of civil servant employees in a Canadian federal organization.…”
Section: Introductionsupporting
confidence: 76%
“…For example, job stress is also found to be predicted by psychological contract [1] (Bocchino, Hartman, & Foley, 2003). Further, the relationship between psychological contract and organizational commitment is also found in previous studies [2] (Gumusluoglu, Karakitapoglu-Aygun, & Hirst, 2013) [3] (Eslami & Gharakhani, 2012). For example, study conducted by [4] ( Lemire & Rouillard, 2005) investigated the relationship between psychological contract violation and organizational commitment in the context of civil servant employees in a Canadian federal organization.…”
Section: Introductionsupporting
confidence: 76%
“…However, much of the research on interactional justice has combined the two types of interactional justice into one factor. For example, interactional justice has positive effects on employee job performance (Shan, Ishaq, & Shaheen, ), engagement and trust (Agarwal, ), and commitment to the supervisor (Gumusluoglu et al, ). However, it remains unclear which effects were specifically from IPJ and which were specifically from IFJ.…”
Section: Discussionmentioning
confidence: 99%
“…Besides paternalistic leadership, these behaviours are compatible with the dimensions of transformational leadership. In fact, recent studies reported that transformational leadership is the most preferred leadership style in Turkey (Aycan & Fikret-Pasa, 2003;Gumusluoglu & Ilsev, 2009;Gumusluoglu, Karakitapoğlu-Aygün, & Hirst, 2013). As in other countries, much of the interest has been devoted to investigate the prevalent and preferred leadership styles in Turkey; however, less attention has been directed to the investigation of how these leadership styles affect employee's perceptions such as perceived empowerment and job satisfaction.…”
Section: Cultural Values and Business Context In Turkeymentioning
confidence: 99%